PROCEDURE FOR MAKING SNAP-ON SMILE WITH ACETYL THERMOPLASTIC RESIN TO IMPROVE THE AESTHETICS AND FUNCTION IN CASE OF TOOTH LOSS - Wahjuni, Sri; Setyowati, Okti; Faisyah, Shilvy Arofatul (Faculty of Vocational Studies, Universitas Airlangga, 2021)
Background: Tooth loss can affect various factors in oral health. Some of these factors are functional, harmonization and aesthetics of oral health. Over time, the aesthetic factor has become an important concern in the manufacture of dentures. Apart from rehabilitating the function and harmonization of oral health, the field of dentistry must also pay attention to the aesthetics of dentures. Purpose: This article aims to discuss the use of acetyl thermoplastic ingredients in making Snap-On Smile. Review: Smile design evaluation of certain elements, namely facial analysis, analysis of relationship between the jaw and face, relationship between teeth and midline of the face, analysis of relationship between teeth and lips, relationship between teeth and gingiva and analysis of shape and color of teeth. All are related to one another. In an ideal smile, the maxillary teeth will show up in the area between the upper and lower lips. Conclusion: Aesthetic and functional improvement in tooth loss can be performed using the Snap-On Smile. Snap-On Smile is a restoration that can be used for aesthetic rehabilitation without requiring preparation or alteration of the tooth structure and cement attachment in its manufacture. The Snap-On Smile prosthesis is more comfortable and can be removed by the patient.